EVALUASI APLIKASI PIJAR SEKOLAH DALAM MENDUKUNG TRANSFORMASI DIGITAL PENDIDIKAN DI KOTA BALIKPAPAN: SYSTEMATIC LITERATUR REVIEW - Hafid Murgantara; ⁠Imanuel Yosua Lonteng; Kasmal Kasmal; Anis Widayati; Ramadiani Ramadiani; Sudarman Sudarman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The digital transformation of education has accelerated the adoption of technology-based learning platforms to enhance the effectiveness of teaching and learning processes as well as school administrative management. One of the emerging platforms in Indonesia is Pijar Sekolah, which provides integrated services for online learning, classroom management, learning assessment, and academic administration. This study aims to analyze the factors influencing the effectiveness of Pijar Sekolah implementation through a Systematic Literature Review (SLR) approach. The study followed the PRISMA 2020 guidelines, including identification, screening, eligibility assessment, and article selection stages. Literature sources were collected from Google Scholar, Garuda, SINTA, and DOAJ, covering publications from 2020 to 2025. A total of 125 articles were identified, and after the selection process, 25 articles met the inclusion criteria and were analyzed. Data were examined using content analysis and narrative synthesis techniques. The findings reveal that system quality, information quality, service quality, ease of use, user satisfaction, and system benefits are the primary factors determining the successful implementation of Pijar Sekolah. System quality emerged as the most influential factor, affecting users’ experiences in accessing and utilizing available services. The review further indicates that the success of digital educational platforms depends not only on the availability of features but also on the system’s ability to effectively and sustainably meet users’ needs. The findings provide valuable insights for improving Pijar Sekolah services and supporting the advancement of digital transformation in education, particularly in Balikpapan City.